Social justice, Islamic state and Muslim countries - Moten, Abdul Rashid (Versita, Warsaw, 2013)
A content analysis of the Qur’an shows that it lays utmost importance on the realization of justice and conversely the eradication of injustice in society. A historical analysis found that social justice was prevalent in Mecca under the leadership of Prophet Muhammad and was also practiced during the period of the first four rightly guided caliphs (Khulafa-e-rashidun). Since then, the successive Muslim majority states have not taken the issue of social justice seriously. These states have failed in taking an active role in uplifting the ethical and moral standards of society. The documentary analysis of the existing 49 states in the Muslim world found majority of these states to have deviated from the real spirit of Islamic social justice falling within the category of “failed states.”